Phenotype of sarcopenic obesity in older individuals with a history of falling. (July 2016) - Huo, Ya Ruth; Suriyaarachchi, Pushpa; Gomez, Fernando; Curcio, Carmen L.; Boersma, Derek; Gunawardene, Piumali; Demontiero, Oddom; Duque, Gustavo
Highlights: Amongst older fallers, sarcopenic obese subjects were older, mostly female and more likely to have lower BMD. Sarcopenic obese individuals have lower grip strength, slower gait velocity, and poor balance. Sarcopenic obese individuals showed higher parathyroid hormone and lower vitamin D. Identification of these particular characteristics would be important to prevent poor outcomes in this high-risk population. Abstract: Background: Although sarcopenic obesity is associated with disability in middle-aged community-dwelling individuals, the phenotype of sarcopenic obesity in people 65 and older, especially those with a history of falls, remain unknown. To fill this knowledge gap, the goal of this study was to obtain a comprehensive phenotype of sarcopenic obesity in this high-risk population. Methods: Cross-sectional study of 680 subjects (mean age = 79 ± 9, 65% female) assessed between 2009 and 2013 at the Falls and Fractures Clinic, Nepean Hospital (Penrith, Australia). The assessment included a comprehensive examination, posturography, gait velocity, grip strength, bone densitometry and body composition by DXA, and blood tests for biochemical status. Patients were divided into four groups based on DXA and clinical criteria: 1) sarcopenic obese; 2) non-sarcopenic obese; 3) sarcopenic and; 4) non-sarcopenic/non-obese. The difference between groups was assessed by one-way ANOVA, chi-square analysis, and multivariable linear regression. Results: Sarcopenic obese subjects were older (81.1 ± 7.3), mostly female and more likely to have lower bone mineral density, lower grip strength, slower gait velocity, and poor balance. Sarcopenic obese individuals also showed significantly higher parathyroid hormone and lower vitamin D. Conclusions: We identified a particular set of clinical and biochemical characteristics in our subgroup of sarcopenic obese older fallers. Identification of these particular characteristics in the clinical setting is essential in order to prevent poor outcomes in this high-risk population.